Strategi Brand Activation pada Brand Minuman Kekinian - Helena Aurora; Sisca Aulia (Kiwari, 2023)
Technology is of course growing rapidly and many companies are competing to use the best strategy for their products so that they have their own uniqueness. This is done so that a brand can easily attract consumers and potential customers. Companies are required to innovate and think creatively so that their products can be easily identified by target consumers. In this study, researchers discussed the pre-launching event Hive It Up by Life of ShuShu in collaboration with influencers, namely Honey Kwok. Through this event, it is necessary to analyze how brand activation is applied in Life of ShuShu. This research is a qualitative descriptive study using the case study method. The data in this study were obtained through observation, documentation, and literature study as well as interviews with informants, namely the marketing team from Life of ShuShu and interviews with invitations to the Hive It Up pre-launching event. The theory used in this research is marketing communications, events, brands, and brand activation. The results of the author's research are to find a strategy from the Life of ShuShu brand that has implemented a brand activation strategy by carrying out forms of brand activation itself so as to achieve the goals desired by Life of ShuShu by collaborating with influencers, namely Honey Kwok because they have similar brand values, and meet market segmentation from Life of ShuShu. Teknologi tentunya semakin berkembang pesat dan banyak perusahaan berlomba-lomba menggunakan strategi terbaik terhadap produknya agar memiliki keunikan tersendiri. Hal ini dilakukan agar suatu brand dapat dengan mudah menarik konsumen maupun calon konsumen. Perusahaan dituntut untuk harus menciptakan inovasi dan berpikir kreatif agar dapat dengan mudah produknya diidentifikasi oleh target konsumen. Peneliti membahas mengenai event pre-launching Hive It Up oleh Life of ShuShu berkolaborasi dengan influencer yaitu Honey Kwok. Melalui event ini perlu dianalisa bagaimana pengaplikasian brand activation pada Life of ShuShu. Penelitian ini merupakan penelitian kualitatif deskriptif menggunakan metode studi kasus. Data pada penelitian ini diperoleh melalui observasi, dokumentasi, dan studi kepustakaan serta wawancara dengan informan yaitu tim marketing dari Life of ShuShu dan wawancara dengan tamu undangan event pre-launching Hive It Up. Teori yang digunakan dalam penelitian ini adalah komunikasi pemasaran, event, brand, dan brand activation. Hasil penelitian penulis yaitu menemukan strategi dari brand Life of ShuShu sudah menerapkan strategi brand activation dengan menjalankan bentuk-bentuk brand activation sendiri sehingga mencapai tujuan yang diinginkan oleh Life Of ShuShu dengan berkolaborasi bersama influencer yaitu Honey Kwok karena memiliki kesamaann brand value, dan memenuhi segmentasi pasar dari Life Of ShuShu.